The SUSTRUS model: a CGE model on regional level for sustainability policies in Russia - Christophe Heyndrickx; Natalia Tourdyeva; Victoria Alexeeva-Talebi (European Regional Science Association (ERSA), 2011)
The present paper describes the construction and first empirical application of the SUSTRUS model (the name of the model refers to "Sustainable Russia"). This model will be the main result of the same-named EU funded project. The SUSTRUS model belongs to the group of regional CGE models, applied to analyze policies with a strong social, economic and environmental dimension. The SUSTRUS model can be used to assist policy makers in their choice of medium and long-term sustainability policies, for the implementation of the EU strategy for sustainable development in Russia as well as an efficient incorporation of the sustainability goals into the existing Russian policy tools on regional and federal levels. The SUSRUS model is constructed as a regional model on federal level, where regions are linked by interregional trade flows, a federal government level and migration. This paper will relate on the calibration of the database for the model and the addition of innovative elements in the model, necessary to model the link between the environmental, social, economic and international modules. The main data sources for the model are the public databases of Rosstat and the micro-level household data from the Russia Longitudinal Monitoring Survey (RLMS). Calibration of the model database was performed by a flexible cross-entropy minimization sub model and standard applied general equilibrium techniques. The general structure of the model will be discussed, focusing on the innovative features of the model and the link between the environmental and economic modules. The application of the model will be shown by a simulation exercise and a presentation of the main results.
Keywords: 330